Mechanism of Electrochemical Delamination of Two-Dimensional Materials from Their Native Substrates by Bubbling - Jie Sun; Xing Fan; Weiling Guo; Lihui Liu; Xin Liu; Jun Deng; Chen Xu (Sensors, 2015)
A capacitor-based circuit model is proposed to explain the electrochemical delamination of two-dimensional materials from their native substrates where produced gas bubbles squeeze into the interface. The delamination is actually the electric breakdown of the capacitor formed between the solution and substrate. To facilitate the procedure, the backside of the ubstrate has to be shielded so that the capacitor breakdown voltage can be reached. The screening effect can be induced either by nonreactive ions around the electrode or, more effectively, by an undetachable insulator. This mechanism serves as a guideline for the surface science and applications involving the bubbling delamination.